Impact of Rejuvenators Type on Physical Properties of Aged Asphalt Cement - Rana Khaled Hamdan; Saad Issa Sarsam (Salehan Institute of Higher Education, 2019)
Recycling can be considered as one of the measures of sustainable methods. The physical traits of the asphalt mixture under the influence of accelerated aging (Long and Short–Term) for asphalt concrete were assessed. Asphalt cement (40-50), aggregate with 12.5 mm nominal extreme size and limestone dust as filler of the mineral was used for the preparation of asphalt concrete mixture. At the optimum content of the asphalt and asphalt of 0.5 percent below and above the optimum value, specimens were prepared by using Marshall Method. Two types of polymers as recycling agents were used (Polyethylene of Low Density and Crumb Rubber) with (0.5, 1 and 1.5) % by weight of the binder. The indirect tensile test was used for the mixtures at 25 ºC and double punch test at 60 ºC. It was determined that the use of (asphalt binder mixed with rubber) as the agent of recycling showed improved performance than the other kind of recycling agent. The indirect tensile strength at 40 ˚C of the recycled mixture was higher than that the control mixture. Punching shear strength was decreased by 84 %, temperature susceptibility was decreased by 69.6 % and the resistance to moisture damage increases by3.3 % at optimum asphalt content.